A4NH 2019 annual report highlights: Flagship 1 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2020)
This includes three highlights document for Flagship 1 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Leading food systems research across CGIAR Highlight 2: Empowering stakeholders for country-level action Highlight 3: Promoting transformation through innovation